2014
DOI: 10.1007/s10826-014-9929-0
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Views on Electronic Mental Health Assessment: Prefer to Type than Talk?

Abstract: For mental health professionals to provide personalized early interventions, young people need to disclose sensitive information to a clinician they are unlikely to have yet formed a relationship with. We conducted in-depth qualitative interviews with 129 young people aged 12–25 years from several sites across Australia to gauge views on whether young people thought that an electronic psychosocial assessment tool could help them initially disclose personal information. Additionally, we were interested in wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 43 publications
(49 reference statements)
7
56
0
Order By: Relevance
“…Participants were also informed of the reasons why young people indicated this as a preference. The full results of this earlier study and the reasons provided by young people are published elsewhere [13].…”
Section: Interview Guidementioning
confidence: 99%
See 3 more Smart Citations
“…Participants were also informed of the reasons why young people indicated this as a preference. The full results of this earlier study and the reasons provided by young people are published elsewhere [13].…”
Section: Interview Guidementioning
confidence: 99%
“…The first was a belief that their clients were somehow distinct from other young people. For example, clinicians questioned who the youth participants were in the prior study described to them which found that young people were open to the use of an e-tool [13]. A typical concern was that clinicians would not be able to safely contain the young person's emotions if they became distressed or that they would not be in a position to quickly clarify misunderstandings: In many cases it was also suggested that young people "don't quite know what they're here for" (female, headspace worker); or that they don't have the capabilities to identify their own areas of risk or concern, "I'm not quite sure that they always can figure out where they are at risk" (female, headspace worker).…”
Section: Engagement Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…This framework is internationally recognised and widely adopted, with expansion of domains at each iteration, evolving from HEADS, to HEADSS, to its current form, HEEADSSS . The questions progress from generally less personal items to more sensitive issues and may assist in the establishment of rapport between the interviewer and the young person . HEEADSSS covers many of the domains represented in psychosocial assessments …”
mentioning
confidence: 99%